The Role of Product Virality in Mediating the Influence of Halal Labels and Prices on Consumer Trust in Somethinc Skincare Products on TikTok Shop - Puspita, Yeza; Sri Wahyuni, Eka; Sumarni, Yenti (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study aims to analyze the influence of halal labels and prices on consumer confidence and test the role of product virality as a mediating variable. The research was conducted in July-November 2025 in Bengkulu City with a quantitative approach. The research population is TikTok users who live in Bengkulu City and have bought Somethinc products through TikTok Shop. The sampling technique used Probability Sampling with the Proportionate Stratified Random Sampling method, with a sample number of 100 respondents determined through the Slovin formula at an error rate of 10%. Data was collected using a Likert-scale questionnaire and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method through the SmartPLS 4 application. The results of the study show that halal labels, prices, and product virality have a positive and significant effect on consumer trust. Price has a significant effect on the virality of the product, while halal labels have no significant effect. Product virality mediates the influence of price on consumer confidence, but does not mediate the influence of halal labels. This research emphasizes the importance of integrating halal aspects, pricing strategies, and viral marketing in building consumer trust in TikTok Shop.